Compressibility of carbon fabrics with needleless electrospun PAN nanofibrous interleaves - S. V. Lomov; K. Molnar (eXPRESS Polymer Letters)
The present paper investigates how the presence of nanofiber interleaves affects the compressibility of the layup during manufacturing of the composites and hence determining the theoretically attainable fiber volume fraction at the given processing pressure. The results show that up to the interleave areal density of 10 g/m2 per nanofiber layer the decrease of fiber volume fraction does not exceed 3% for a laminate of carbon fiber woven fabric. Interleaves inside a fabric laminate are more compressible than a plain electrospun veil. It can be explained as the nanofibers penetrate between the carbon fibers when applying compression during composite manufacturing. It can be stated that there is a strong interference between the interleaves and the carbon reinforcement, which can lead to effective toughness improvement of the composite without significant alteration of fiber volume content.